TEACHERS' PERCEPTIONS TOWARD PICTURES USAGE AND STUDENTS’ VISUALSPATIAL INTELLIGENCE IN TEACHING VOCABULARY - Wirathama Hazera Putra; Yuliasari Yuliasari; Susanto Susanto (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
This research discusses the teachers’ perceptions toward the contribution of vocabulary teaching with pictures for students’ visual-spatial intelligence. Visual-spatial intelligence is the potential for representing the spatial world internally in one’s mind as used in reading maps and charts, drawing, solving mazes and puzzles, imagining and visualizing. This research is qualitative research. The data was analysis by combining the result from the questionnaire and interview. Based on the results of the questionnaires and interviews, the teachers agreed that teaching vocabulary with pictures made their students more interested and active. They also agree that this method has a positive impact on the learning process of teaching vocabulary. In addition, the teachers stated that teaching vocabulary using pictures was very helpful and contributed to them in attracting students' attention. According to them, teaching using images is very important for students who have their visual-spatial intelligence. With this method, it becomes easier for them to imagine the form of a picture from a vocabulary.